Etika Protes dalam Perspektif Hadis - Nurnazilatul Wahdah; Repa Hudan Lisalam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
A discussion on Islamic morality and ethics is the purpose of this paper. We see many modern generations paying little attention to how to apply morality in their daily lives. Morals and ethics are human behaviours in daily life that have been instilled. Morals come from the Qur'an and the Hadith of the Prophet Muhammad and include what is good, bad, right, and wrong in one's actions. Meanwhile, ethics come from the culture and customs of the local community. In this paper, the author discusses the meaning of morals and ethics, human relationships with God, humans, and nature. Protest is a legitimate form of expression in a democratic society. In Islam, protest is also recognised as the right of everyone to voice injustice and bias. However, protests must also be carried out with ethics that are in accordance with Islamic teachings. The ethics of protest can be explained in the hadith, namely: Protests must be carried out peacefully and not violate the law. This is in accordance with the hadith of the Prophet Muhammad SAW,